A Critical Review of Properties of Darunavir and Analytical Methods for Its Determination - Ruela Correa, Josilene Chaves [UNESP]; D'Arcy, Deirdre M.; Reis Serra, Cristina Helena dos; Salgado, Hérida Regina Nunes [UNESP] (Taylor & Francis Inc, 2014)
Darunavir is a synthetic non-peptidic protease inhibitor that has been shown to be extremely potent against wild-type HIV, and it is an important component of highly active antiretroviral treatment (HAART), which is considered as one of the most significant advances in the field of HIV therapy. However, there are some concerns about darunavir quality control. Darunavir shows pseudo-polymorphism: in different ambient conditions one pseudo-polymorphic form can change to another. This behavior of darunavir is problematic because the dosage form is exposed to different ambient conditions around the world, since HIV/AIDS is prevalent globally. Issues around differences in the solubility and effects that different forms of darunavir can cause are of concern, and a more stable form is preferable. Important investigations of darunavir such as dissolution behavior, polymorphism, stability and degradation studies, and the impact of that on the quality of the product are being conducted by our working group. A cure for HIV/AIDS remains a long-term commitment, and there is much yet to achieve. This article discusses, by a critical review of the literature, the impact of the use of darunavir in the treatment of HIV-infected patients, its physical-chemical properties, the analytical methods to determine it, and challenges that remain in order to ensure the quality and stability of darunavir.
Keywords: Darunavir; HPLC (high-performance; pressure liquid chromatography); physicochemical properties; quality control; stability